Optimized allosteric inhibition of engineered protein tyrosine phosphatases with an expanded palette of biarsenical small molecules. Issue 9 (15th May 2018) - Korntner, Samuel; Pomorski, Adam; Krężel, Artur; Bishop, Anthony C.
Graphical abstract: Abstract: Protein tyrosine phosphatases (PTPs), which catalyze the dephosphorylation of phosphotyrosine in protein substrates, are important cell-signaling regulators, as well as potential drug targets for a range of human diseases. Chemical tools for selectively targeting the activities of individual PTPs would help to elucidate PTP signaling roles and potentially expedite the validation of PTPs as therapeutic targets. We have recently reported a novel strategy for the design of non-natural allosteric-inhibition sites in PTPs, in which a tricysteine moiety is engineered within the PTP catalytic domain at a conserved location outside of the active site. Introduction of the tricysteine motif, which does not exist in any wild-type PTP, serves to sensitize target PTPs to inhibition by a biarsenical compound, providing a generalizable strategy for the generation of allosterically sensitized ( as ) PTPs. Here we show that the potency, selectivity, and kinetics of as PTP inhibition can be significantly improved by exploring the inhibitory action of a range of biarsenical compounds that differ in interarsenical distance, steric bulk, and electronic structure. By investigating the inhibitor sensitivities of five as PTPs from four different subfamilies, we have found that as PTP catalytic domains can be broadly divided into two groups: one that is most potently inhibited by biarsenical compounds with large interarsenical distances, such as AsCy3-EDT2, and one that is most potently inhibited by compounds with relatively small interarsenical distances, such as FlAsH-EDT2 . Moreover, we show that a tetrachlorinated derivative of FlAsH-EDT2, Cl4FlAsH-EDT2, targets as PTPs significantly more potently than the parent compound, both in vitro and in as PTP-expressing cells. Our results show that biarsenicals with altered interarsenical distances and electronic properties are important tools for optimizing the control of as PTP activity and, more broadly, suggest that diversification of biarsenical libraries can serve to increase the efficacy of these compounds in targeted control of protein function.